2020
DOI: 10.1016/j.gca.2020.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Identifying thermogenic and microbial methane in deep water Gulf of Mexico Reservoirs

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…(3) methanogenesis is commonly associated with hydrocarbon biodegradation (sometimes referred to as 'secondary methanogenesis'; e.g., Jones et al, 2008), and compound-specific stable isotope signatures indicate significant microbial input of methane; that is to say, δD and δ 13 C of methane in these samples match a microbial origin in a 'Schoell/Whiticar diagram' (Figure 1; Whiticar, 1999), and δ 13 C of methane has a negative anomaly (compared to δ 13 C trend of C2+ alkanes) in a 'Chung plot' ( Figure A2); and (4) apparent temperatures derived from Δ 18 -clumped isotope measurements of methane are between 30-68 °C (Figure 7), consistent with the reservoir temperatures of these wells (42-59 °C), suggesting that these methanes were formed (or microbially recycled) in situ (see Thiagarajan et al, 2020a). Although microbial methane is often in clumped isotope disequilibrium Wang et al, 2015;Douglas et al, 2016;Young et al, 2017), microbial methane found in marine and/or subsurface environments is usually in or close to equilibrium.…”
Section: Biological Degradationmentioning
confidence: 73%
See 1 more Smart Citation
“…(3) methanogenesis is commonly associated with hydrocarbon biodegradation (sometimes referred to as 'secondary methanogenesis'; e.g., Jones et al, 2008), and compound-specific stable isotope signatures indicate significant microbial input of methane; that is to say, δD and δ 13 C of methane in these samples match a microbial origin in a 'Schoell/Whiticar diagram' (Figure 1; Whiticar, 1999), and δ 13 C of methane has a negative anomaly (compared to δ 13 C trend of C2+ alkanes) in a 'Chung plot' ( Figure A2); and (4) apparent temperatures derived from Δ 18 -clumped isotope measurements of methane are between 30-68 °C (Figure 7), consistent with the reservoir temperatures of these wells (42-59 °C), suggesting that these methanes were formed (or microbially recycled) in situ (see Thiagarajan et al, 2020a). Although microbial methane is often in clumped isotope disequilibrium Wang et al, 2015;Douglas et al, 2016;Young et al, 2017), microbial methane found in marine and/or subsurface environments is usually in or close to equilibrium.…”
Section: Biological Degradationmentioning
confidence: 73%
“…Left panel: gases with potential microbial methane input and/or hydrocarbon consumption. (See Thiagarajan et al (2020a) and Section 5.4.2 of this paper); Right panel: gases of thermogenic origin.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…Produced water samples were collected from production wells in the Hoover Field in the Hoover-Diana mini-basin located at the intersection of the Alaminos Canyon and East Breaks area of the western United States Gulf of Mexico. These wells are at 1400-1500 m water depth and the Hoover reservoir has a reported temperature of approximately 68 • C (Thiagarajan et al, 2020). Oil and oil-solution gas are hosted in Plio-Pleistocene age reservoirs, and have been previously reported to be sourced from a Tertiary marine source interval (Hood et al, 2002).…”
Section: Sample Sitementioning
confidence: 99%
“…Based upon the molecular and isotopic composition of methane, ethane, propane, and butane (Stahl, 1977;Bernard et al, 1978;Schoell, 1980;Chung et al, 1988;Schoell, 1988;Hunt, 1996;Whiticar, 1999;Milkov, 2011), geological natural gas can be categorized in three main classes microbial (e.g., Thiagarajan et al, 2020) thermogenic (e.g., Etiope et al, 2013a), and abiotic (e.g., Etiope et al, 2013b).…”
Section: Types Of Natural Gas From Seepagesmentioning
confidence: 99%
“…Several different types of fluids that escape from the seabed have been surveyed and studied: (i) hydrothermal fluids (e.g., Tao et al, 2020); (ii) geological hydrocarbon, methane-rich gas of microbial, thermogenic or mixed (e.g., Thiagarajan et al, 2020) and abiotic origin (Sciarra et al, 2019); (iii) modern microbial (e.g., Deville et al, 2020); (iii) freshwater discharges (Christodoulou et al, 2003;Whiticar, 2002); (iv) porewater escape (Harrington, 1985); (v) gas and oil saturated water and mud discharges from mud volcanoes (e.g., Chen et al, 2020).…”
Section: Seabed Fluid Flowmentioning
confidence: 99%